Lumbosacral spinal compression device with the use of a cushion back support in supine MRI - Sungkarat, Witaya; Laothamatas, Jiraporn; Worapruekjaru, Ladawan; Hooncharoen, Boonthida; Charoensuk, Jarruwat; Chousangsuntorn, Khaisang (My University, 2021)
Background: We hypothesized that axial-loaded magnetic resonance imaging (MRI), modified with the use of a cushion placed behind the lower back (i.e. BS-MRI method), would simulate the standing position more accurately than an axial-loaded MRI without a cushion back support (BS). Purpose: To determine whether the BS-MRI method demonstrated similar morphologies on intervertebral disc (IVD), dural sac, and spinal curvature as those detected on 90° standing MRIs in individuals with suspected spinal stenosis. Material and Methods: Twenty-five subjects underwent a BS-MRI, as well as axial-loaded and standing MRI studies. Outcome measures were four radiographic parameters of the lumbar spine: IVD height (DH); dural sac cross-sectional area (DCSA); and spinal curvature (i.e. lumbar lordosis [LL] and L1-L3-L5 angle [LA]). Results: Major differences (>5%) between standing MRI and BS-MRI methods were observed in DCSA, DH, and LL. Major differences between standing and axial loaded MRIs were observed only in DCSA and LA. Although BS-MRIs demonstrate an image of the lumbar spine curvature (i.e. LA) which is closer to that when standing than axial-loaded MRIs, it is likely to overestimate both narrowing of dural sac and extent of LL. Conclusion: Using a compression device with a BS to simulate weight-bearing on the lumbar spine is not recommended due to: (i) overestimation of the narrowing of the dural sac and extent of LL; and (ii) underestimation of loss of disc height. Supine axial-loading produced DCSA and DH which were strongly correlated with those detected with standing MRIs. Exceptions were that LL and LA were underestimated.
Keywords: Axial loading; cushion back support; low back pain; lumbar lordosis; spinal stenosis; upright magnetic resonance imaging